1999
DOI: 10.1006/reec.1999.0187
|View full text |Cite
|
Sign up to set email alerts
|

Recent results on belief, knowledge and the epistemic foundations of game theory

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 53 publications
2
88
0
Order By: Relevance
“…The following EDLA formula characterizes a notion of rationality which is commonly supposed in epistemic analysis of games (see, e.g., [3,5]):…”
Section: Epistemic Rationalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The following EDLA formula characterizes a notion of rationality which is commonly supposed in epistemic analysis of games (see, e.g., [3,5]):…”
Section: Epistemic Rationalitymentioning
confidence: 99%
“…Our logic supports reasoning about epistemic games in strategic form in which agents decide what to do according to some general principles of rationality while being uncertain about several aspects of the interaction such as other agents' choices, other agents' preferences, etc. Although epistemic games have been extensively studied in economics in the so-called area of interactive epistemology (see, e.g., [1,10,9,3,11]) and there have been some analysis of epistemic games in modal logic (see, e.g., [5,12,9,21]), no modal approach to epistemic games in strategic form has been proposed up to now which addresses all the following issues at the same time: to provide a formal language, and a corresponding formal semantics, which is sufficiently general to express solution concepts like Nash Equilibrium or Iterated Deletion of Strictly Dominated Strategies (IDSDS) and to deduce formally the epistemic and rationality conditions on which such solution concepts are based; to prove its soundness and completeness; to study its computational properties like decidability and complexity. In this paper, we try to fill this gap by proposing a sound and complete modal logic for epistemic games interpreted on a Kripke-style semantics.…”
Section: Introductionmentioning
confidence: 99%
“…16 Thus, if at a state ω there is common belief of rationality then, for every player i, σ i (ω) survives the iterated deletion of strictly dominated strategies. For more details on this result, which originates in Bernheim (1984) and Pearce (1984), and relevant references, see Battigalli and Bonanno (1999), Bonanno (forthcomingb), Dekel and Gul (1997), Perea (2012). 17 For an extensive discussion see Halpern (1999b).…”
Section: G Bonannomentioning
confidence: 92%
“…Such functions are called possibility correspondences (or information functions) in the game-theoretic literature. 7 For more details see the survey in Battigalli and Bonanno (1999). 8 In modal logic belief operators are defined as syntactic operators on formulas.…”
Section: Rational Playmentioning
confidence: 99%
“…There is a substantial amount of research within game theory on the implications of assumptions concerning players' knowledge and beliefs [5]. In particular, Tan and Werlang [16] have shown that if payoffs are commonly known and all players are rational and commonly believe in each other's rationality, they will only play strategies that survive iterated elimination of strictly dominated strategies (IESDS).…”
Section: Background and Motivationmentioning
confidence: 99%